Contribution of Household’s Member To Fisherman’s Household Income Of Bukit Batu District Bengkalis Regency Riau Province - Purwantoro '; Firman Nugroho; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Research was conducted In of Bukit Batu District Bengkalis Regency Riau Province April 2014. This study aimed to find out the characteristics of the fishermen and contribution level given by the household’s members. Method used in this research is survey method by observing and collecting data through interviews ith fishermen of bukit batu district, equipped with a questionnaire (a list of questions), 34 fishermen respondents comprised 8 owners and 26 workers.The characteristics of fishermen observed were age 38 - 45 years old, formal eduction taken was 6 years (elentary school graduates only), with working experience of 25 years, household’s incomes of IDR 2.078.000. Contribution level of households for fishermen (owner) was 84,34% husbands, 2,86% wives, and 12,8% children. Meanwhile, contribution level of household member for fishermen (worker) was 62,46% husbans, 19,67% wives, and 17,87% children.Keywords: Contribution, households, earnings.